(untitled) (Journal of history, 2023)
This article examines the personal development of Nazir Torekulov during his years of study at the Moscow Commercial Institute, who, having failed to take his place in the history of the country, reunited with his people only when we became an independent state. One of the periods in the life of Nazir Torekulov, a figure who worked tirelessly in the interests of the people, pointing the way to the future of his nation, was historically analyzed on the basis of new archival documents, publications and research papers. Cause-and-effect relationships are revealed between the life of a Kazakh figure, who held a high position of Soviet power, and the education acquired at the Moscow Commercial Institute, knowledge of languages ​​and the beginning of his direct participation in the socio-political processes of the country. When considering a certain stage of personality formation, methods of comparative analysis, forecasting, analysis were used, aimed at identifying the content of historical data and established facts on the basis of general scientific and historical principles.The novelty of the scientific article can be attributed to the scientific restoration of the true picture of the life and social activities of a historical person on the basis of reliable data and new archival documents. The results of the study will be used to summarize the data collected about Nazir Torekulov in domestic historical science and for methodological guidance.